The Bible and Theology - Leith, John Haddon (Interpretation, 1976)
The dependence of Christian theology on the Scriptures cannot be stated in tenus of some one method of using them. But there are features of the relationship which belong to the right and true understanding of them that is faithful to what the Christian community recognized as the decisive revelation of God.